Crescents proportions above 10% are associated with unfavorable kidney outcomes in IgA nephropathy patients with partial crescent formation - Dingxin Di; Lin Liu; Ying Wang; Yue Yang; Shimin Jiang; Wenge Li (Renal Failure, 2023)
Purpose Whether different crescentic proportions determine the progression of IgA nephropathy (IgAN) with crescents in less than 50% of glomeruli remains controversial. We aimed to evaluate the relationship between different proportions of crescents and kidney outcomes in IgAN with partial crescent formation.Methods Patients diagnosed as IgAN, having at least two crescents and in less than 50% of glomeruli, were categorized into three groups: Group I (crescents in ≤10% of glomeruli), Group II (10%< crescents ≤25% of glomeruli) and Group III (crescents >25% of glomeruli). Baseline clinicopathological parameters were evaluated. The kidney endpoint was a composite of a ≥ 40% decline in the initial estimated glomerular filtration rate, end-stage kidney disease, and kidney disease-related death.Results Of 183 IgAN patients with crescents in less than 50% of glomeruli, baseline 24-hour urinary protein and immunosuppressive treatment varied among the three groups (p < 0.05). During a median follow-up of 57 months (interquartile range 28–86), 50 (27.3%) patients reached the composite outcome. Kaplan–Meier survival analysis revealed that kidney survival in Group II (p = 0.049) and Group III (p = 0.008) was significantly shorter than in Group I, with no significant difference between Group II and III (p = 0.2). After adjusting for clinical factors and MEST score based on the multivariate Cox regression analysis, a crescent proportion >10% (HR = 3.431, 95% CI 1.067–11.03, p = 0.039) was predictive of time to unfavorable kidney outcome, with model adjustments improving predictability (c-index: 0.817).Conclusion The proportion of crescents reaching 10% of glomeruli in IgAN was identified as an independent risk factor for kidney survival.